Composite powder with core-shell structure and preparation method thereof
By pretreating nickel powder, titanium dioxide coating and silver coating, a composite powder with a core-shell structure is formed, which solves the problems of nickel powder unevenness and poor cladding density, and improves the conductivity and stability of MLCC sex.
Patent Information
- Application Number
- CN202411460484.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-18
AI Technical Summary
In multi-layer ceramic capacitors (MLCCs), the unevenness of nickel powder and high temperature oxidation lead to poor cladding density, affecting conductivity and stability.
The preparation method of composite powder using core-shell structure includes pretreatment of nickel powder, titanium dioxide coating treatment and silver coating treatment. Through ultrasonic stirring and constant temperature reaction, titanium dioxide coating nickel powder is formed and silver atoms are used on the titanium dioxide layer. Deposition increases the density and conductivity of the cladding.
It improves the stability of nickel powder and the denseness of the coating layer, reduces the resistivity and high-temperature oxidation resistance of the composite powder, and enhances its application performance in the field of MLCC.
Smart Images

Figure CN119319244A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal composite materials, and in particular to a composite powder with a core-shell structure and a preparation method thereof. Background Art
[0002] Multilayer ceramic capacitors (MLCC), also known as chip capacitors, multilayer capacitors, and stacked capacitors, are the most widely used capacitors in modern electronic devices. MLCC is formed by stacking ceramic dielectric diaphragms with printed electrodes (inner electrodes) in an interlaced manner, sintering at high temperature to form a ceramic block, and then sealing the two ends of the ceramic block with a metal layer (outer electrode). In the process of manufacturing the inner electrode, the metal particles are first mixed with a glass phase, a dispersant, etc. to form a slurry. In this process, if the uniformity of the metal particles is not good, it will affect the uniformity of the thickness of the electrode after subsequent printing and sintering; if the metal particles interact with each other or with other particles to cause the particles to agglomerate, then breakdown will occur during the lamination process.
[0003] Nickel, as the main material currently used in this field, needs to be co-fired with electrolyte materials (barium titanate) at high temperatures to form electrode layers and dielectric layers. However, nickel is easily oxidized in the air at high temperatures, so it must be sintered in a reducing atmosphere. However, traditional barium titanate materials are prone to forming oxygen vacancies under the action of a reducing atmosphere, resulting in a loose coating layer and poor compactness. Based on this, how to improve the stability of nickel powder during the preparation process and the compactness of the coating layer is the research focus of MLCC applications. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a composite powder with a core-shell structure and a preparation method thereof, which can effectively improve the stability of nickel powder and the density of the coating layer during the preparation of the composite powder, thereby facilitating the improvement of the electrical conductivity of the composite powder.
[0005] In order to achieve the above purpose, one of the technical solutions adopted by the present invention is: a method for preparing a composite powder with a core-shell structure, comprising sequentially performing pretreatment, titanium dioxide coating treatment, plating solution treatment, and silver coating treatment on nickel powder, wherein: The titanium dioxide coating treatment comprises: adding butyl titanate and anhydrous ethanol in a reaction container in sequence, stirring and dispersing with ultrasonic stirring, and then adding dilute acid to obtain a reaction solution; adding the pretreated nickel powder into the reaction solution for constant temperature reaction, and after the reaction, sequentially performing solid-liquid separation, washing, and drying to obtain titanium dioxide coated nickel powder; The plating solution treatment comprises: adding titanium dioxide coated nickel powder, solvent and dispersant in a reaction container in sequence, stirring and dispersing by ultrasonic stirring, and then moving to an oil bath pot for constant temperature stirring, adding a reducing agent and sodium hydroxide solution during the constant temperature stirring process, and obtaining a dispersed solution after reaction; The silver coating treatment comprises: taking another reaction container and adding silver nitrate and deionized water, after ultrasonic stirring and dispersion, adding a complexing agent to carry out a complexing reaction; under stirring, slowly adding the complexed silver source reaction liquid to the dispersed solution for reaction, and after the reaction, sequentially performing solid-liquid separation, washing, and drying to obtain a composite powder.
[0006] The beneficial effects of the method for preparing the composite powder with a core-shell structure of the present invention are: 1. First, the nickel powder can be surface treated by pretreatment to remove impurities on the surface of the nickel powder, so that the nickel powder participating in the subsequent treatment is purer; then, a layer of titanium dioxide is coated on the surface of the nickel powder by titanium dioxide coating treatment, so that the titanium dioxide coated nickel powder has the dual properties of titanium dioxide and nickel; then, the titanium dioxide coated nickel powder is treated by plating solution to allow the titanium dioxide coated nickel powder to participate in the subsequent silver coating treatment in the form of chemical plating, so as to achieve the deposition of silver atoms on the surface of the titanium dioxide coated nickel powder; and because of the coating of silver atoms on the titanium dioxide coated nickel powder, the deposition of silver atoms on the surface of the titanium dioxide coating layer can be used to coat and fill the oxygen vacancies on the surface of the titanium dioxide coating layer, while improving the density of the coating layer, the good electrical conductivity of silver atoms is used to reduce the resistivity and high-temperature oxidation resistance of the composite powder.
[0007] 2. In the silver coating process, the addition of the complexing agent can slow down the deposition rate of silver atoms, so that the silver atoms can be better coated on the surface of the titanium dioxide coated nickel powder. In the plating solution treatment, the addition of the sodium hydroxide solution can adjust the pH value of the dispersed solution to reduce the phenomenon of hindering the silver deposition coating caused by the adsorption of complex ions on the particle surface during the silver coating process. In addition, by using titanium dioxide as an intermediate transition layer between nickel and silver, the lower high-temperature expansion coefficient of titanium dioxide can be utilized to reduce the probability of deformation of the composite powder during high-temperature sintering. The thickness of the intermediate transition layer titanium dioxide can be adjusted by changing the amount of butyl titanate added, thereby making the titanium dioxide coating uniform, which is beneficial to the subsequent silver coating.
[0008] 3. The preparation method of the present invention has low cost, simple process, and is easy to operate. The prepared composite powder can have the properties of nickel, titanium dioxide and silver, and can be better used in the MLCC field.
[0009] Further, the pretreatment includes degreasing treatment, roughening treatment and activation treatment performed in sequence, wherein the degreasing treatment includes adding nickel powder and surface cleaning agent into a reaction vessel, standing and settling after ultrasonic stirring for solid-liquid separation, and washing the settled nickel powder multiple times with deionized water; the roughening treatment includes sequentially adding degreasing nickel powder and dilute acid into a reaction vessel, standing and settling after ultrasonic stirring for solid-liquid separation, and washing the settled nickel powder multiple times with deionized water; the activation treatment includes sequentially adding coarsening nickel powder, deionized water, and surfactant into a reaction vessel, stirring at a constant temperature until the reaction is completed, standing and settling for solid-liquid separation, and washing the settled nickel powder multiple times with deionized water. The degreasing treatment can remove the oil stains on the surface of the nickel powder, the roughening treatment can remove the oxide layer on the surface of the nickel powder, and the activation treatment can improve the activation performance of the nickel powder, which is beneficial to the coating of titanium dioxide on the surface of the nickel powder particles.
[0010] Furthermore, during the degreasing treatment, the surface cleaning agent uses at least one of citric acid, dodecylphenol polyoxyethylene ether, anhydrous ethanol, lauric acid alkylamine phosphate, and fatty alcohol ether sodium sulfate, and the mass ratio of the surface cleaning agent to the nickel powder is 0.01 to 1:1.
[0011] Furthermore, during the roughening treatment, the dilute acid is one of dilute sulfuric acid, dilute acetic acid, and dilute hydrochloric acid, and the mass ratio of the dilute acid to the nickel powder after the degreasing treatment is 5 to 15:1.
[0012] Furthermore, during the activation treatment, the surfactant is a silane coupling agent, and the mass ratio of the surfactant to the nickel powder after the roughening treatment is 0.01 to 1:1. Furthermore, during the titanium dioxide coating treatment, the mass ratio of the dilute acid to butyl titanate is 0.1 to 1:1, and the temperature of the isothermal reaction is 20 to 80°C.
[0013] Furthermore, during the plating solution treatment, the solvent is at least one of deionized water, anhydrous ethanol, ethylene glycol, and propylene glycol, the dispersant is at least one of polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfate, and ammonium citrate, and the reducing agent is at least one of glucose, L-ascorbic acid, hydrazine hydrate, and sodium hypophosphite.
[0014] Furthermore, during the plating solution treatment, the amount of sodium hydroxide solution added is such that the pH value of the dispersed solution is maintained between 12 and 13.
[0015] Furthermore, during the silver coating treatment, the complexing agent is at least one of ammonia water, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, diethylenetriamine, and triethylenetetramine, and the mass ratio of the complexing agent to silver nitrate is 1 to 50:1. The second technical solution adopted by the present invention is: a composite powder with a core-shell structure, which is prepared by any of the above-mentioned preparation methods. The composite powder of the present invention can have both the anti-reduction property of titanium dioxide and the high conductivity of silver on the basis of nickel powder through two coatings (one titanium dioxide coating and one silver coating), so that the composite powder can be better used in the field of conductive paste and MLCC. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is an electron microscope scanning image of the composite powder of Example 1 of the present invention; Figure 2 This is an electron microscope scanning image of the composite powder of Example 2 of the present invention; Figure 3 This is an electron microscope scanning image of the composite powder of Example 3 of the present invention; Figure 4 This is an electron microscope scanning image of the composite powder of Comparative Example 1 of the present invention; Figure 5 This is an electron microscope scanning image of the composite powder of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0016] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0017] Example The present invention provides a method for preparing a composite powder with a core-shell structure, comprising sequentially performing pretreatment, titanium dioxide coating treatment, plating solution treatment, and silver coating treatment on nickel powder. Specifically, The pretreatment includes degreasing treatment, roughening treatment and activation treatment performed in sequence, wherein the degreasing treatment includes adding nickel powder and surface cleaning agent into a reaction vessel (such as a beaker), ultrasonic stirring, and then letting the reaction vessel settle for solid-liquid separation, and washing the settled nickel powder multiple times with deionized water. Furthermore, the surface cleaning agent uses at least one of citric acid, dodecylphenol polyoxyethylene ether (OP-10), anhydrous ethanol, lauric acid alkylamine phosphate, and fatty alcohol ether sodium sulfate, and the mass ratio of the surface cleaning agent to the nickel powder is 0.01 to 1:1. Exemplarily, the mass ratio of the surface cleaning agent to the nickel powder can be 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.4:1, 0.8:1 or 1:1.
[0018] The roughening treatment includes adding the deoiled nickel powder and dilute acid into the reaction vessel, standing and settling after ultrasonic stirring for solid-liquid separation, and washing the settled nickel powder with deionized water for multiple times until the pH value of the washing solution is neutral. Furthermore, the dilute acid is one of dilute sulfuric acid, dilute acetic acid, and dilute hydrochloric acid, and the mass ratio of the dilute acid to the deoiled nickel powder is 5 to 15:1. Exemplarily, the mass ratio of the dilute acid to the nickel powder can be 5:1, 7:1, 9:1, 10:1, 11:1, 13:1 or 15:1.
[0019] The activation treatment includes adding the nickel powder after the roughening treatment, deionized water, and a surfactant to a reaction vessel, stirring at a constant temperature until the reaction is completed, standing and settling for solid-liquid separation, and washing the settled nickel powder multiple times with deionized water. Furthermore, the surfactant is at least one of silane coupling agent KH550, silane coupling agent KH560, silane coupling agent KH570, and silane coupling agent KH590. The mass ratio of the surfactant to the nickel powder after the roughening treatment is 0.01 to 1:1. Exemplarily, the mass ratio of the surfactant to the nickel powder can be 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.4:1, 0.8:1 or 1:1.
[0020] The titanium dioxide coating treatment includes: taking another reaction container (such as a beaker), adding butyl titanate and anhydrous ethanol in the reaction container in sequence, stirring and dispersing with ultrasonic stirring, and then adding dilute acid to obtain a reaction solution; adding the pretreated nickel powder to the reaction solution for isothermal reaction, standing and settling after the reaction to separate the solid and liquid, and then washing with anhydrous ethanol and placing in a high-temperature drying oven for drying to obtain titanium dioxide coated nickel powder. Furthermore, the dilute acid can be one of dilute sulfuric acid, dilute acetic acid, and dilute hydrochloric acid, and the mass ratio of dilute acid to butyl titanate is 0.1 to 1:1, such as 0.1:1, 0.3:1, 0.5:1, 0.8:1 or 1:1. The temperature of the isothermal reaction is 20 to 80°C, such as 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C.
[0021] The plating solution treatment includes adding titanium dioxide coated nickel powder, solvent, and dispersant in a reaction container in sequence, moving the mixture to an oil bath for constant temperature stirring after ultrasonic stirring, adding a reducing agent during the constant temperature stirring process, and adding sodium hydroxide solution to adjust the pH value of the solution, and obtaining a dispersed solution after the reaction.
[0022] The solvent is at least one of deionized water, anhydrous ethanol, ethylene glycol, and glycerol. The mass ratio of the solvent to the nickel in the titanium dioxide-coated nickel powder is 10 to 100:1, such as 10:1, 20:1, 30:1, 40:1, 50:1, 75:1, or 100:1.
[0023] The dispersant is at least one of polyvinyl pyrrolidone, polyethylene glycol 200, polyethylene glycol 2000, sodium lauryl sulfate, and ammonium citrate. The mass ratio of the dispersant to the nickel in the titanium dioxide-coated nickel powder is 0.001 to 1:1, such as 0.001:1, 0.01:1, 0.1:1, 0.2:1, 0.5:1, 0.8:1, and 1:1.
[0024] The reducing agent is at least one of glucose, L-ascorbic acid, hydrazine hydrate and sodium hypophosphite. The mass ratio of the reducing agent to silver nitrate is 0.1 to 10:1, such as 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 5:1, 10:1.
[0025] Furthermore, the amount of sodium hydroxide solution added is such that the pH value of the dispersed solution is maintained between 12 and 13, so as to reduce the adsorption of nickel ammine complex ions and silver ammine complex ions on the particle surface during the subsequent complex reaction of the dispersed solution with silver nitrate and the complexing agent, thereby affecting the deposition and coating of silver atoms.
[0026] The silver coating treatment includes: taking another reaction container (such as a beaker), adding silver nitrate and deionized water into the reaction container, after ultrasonic stirring and dispersion, adding a complexing agent for complexing reaction; then slowly adding the complexed silver source reaction solution to the dispersed solution under stirring, and after the reaction is completed, standing and settling to separate the solid and liquid, and washing the solution with deionized water until it is clear, and then washing it twice with anhydrous ethanol and drying it in a 60°C forced air drying oven for 3 to 6 hours to obtain a composite powder.
[0027] Wherein, the complexing agent is at least one of ammonia water, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, diethylenetriamine, and triethylenetetramine, and the mass ratio of the complexing agent to silver nitrate is 1 to 50:1, for example, 1:1, 5:1, 10:1, 20:1, 30:1, 40:1 or 50:1. The present invention removes oil, removes the oxide layer and performs activation treatment on the surface of the nickel powder at one time through pretreatment, so that titanium dioxide is coated on the surface of the nickel powder particles, and then silver is deposited on the surface of the titanium dioxide-coated nickel powder by chemical plating, so as to reduce oxygen vacancies on the surface of the titanium dioxide by doping with silver metal, inhibit the crystallization of titanium dioxide and other phases, and at the same time improve the conductivity of the composite powder.
[0028] Example 1 The composite powder 1 was prepared by the following steps: Step 1: Add 1g citric acid and 1000mL deionized water to a beaker in sequence, stir to dissolve, add 10g nickel powder to the citric acid solution, stir ultrasonically, and then let it stand to settle, then wash twice with anhydrous ethanol and three times with deionized water for use.
[0029] Step 2: Add 1000 mL of deionized water and 10 g of 98.3% sulfuric acid in a beaker, stir and mix, then add the nickel powder treated in step 1, perform ultrasonic stirring for 30 minutes (the frequency of the ultrasonic cleaning machine is 50 kHz), then let it stand and settle for solid-liquid separation, and wash with deionized water until the solution is neutral for use.
[0030] Step 3: Add 1000 mL of deionized water and 1 g of silane coupling agent KH550 to a beaker and stir to mix. Then add the nickel powder cleaned in step 2 and stir to react at 40 °C for 5 hours. After the reaction is completed, let it stand and settle for solid-liquid separation, wash with anhydrous ethanol 3-5 times, and then use deionized water to wash until the solution is clear for use.
[0031] Step 4: Add 10 g of butyl titanate and 1000 mL of anhydrous ethanol into a beaker, stir to mix, then add 10 g of 36.5% dilute acetic acid and the nickel powder cleaned in step 3 in sequence, stir at 500 rpm, add 50 g of deionized water at a rate of 1 ml / min, continue the reaction for 2 h after the addition is completed, let it stand and settle for solid-liquid separation, and wash with ethanol 3-5 times. The washed wet powder is placed in a high-temperature drying oven and dried at 60 °C to obtain titanium dioxide-coated nickel powder.
[0032] Step 5: Add the titanium dioxide-coated nickel powder obtained in step 4, 1000 mL of deionized water and 1 g of ammonium citrate to a beaker in sequence and stir for 30 min. Then move to an oil bath, add 4 g of glucose and stir at 80°C to prepare a dispersed solution. Add sodium hydroxide solution during the process to adjust the pH value of the solution to 12-13. Step 6: Take another beaker, add 10 g of silver nitrate and 1000 mL of deionized water into the beaker, stir ultrasonically, then add 20 g of ethylenediaminetetraacetic acid and stir for 30 min, add the complexed silver source into the dispersed solution in step 5, stir at 80°C and 300 rpm, after the reaction, settle to separate the solid and liquid, wash the solution with deionized water until it is clear, wash it twice with anhydrous ethanol, and place it in a 60°C forced air drying oven for 6 h to obtain the following: Figure 1 The composite powder 1 shown.
[0033] Example 2 Step 1: Add 1g citric acid and 1000mL deionized water to a beaker in sequence, stir to dissolve, add 10g nickel powder to the citric acid solution, stir ultrasonically, and then let it stand to settle, then wash twice with anhydrous ethanol and three times with deionized water for use.
[0034] Step 2: Add 1000 mL of deionized water and 10 g of 98.3% sulfuric acid in a beaker, stir and mix, then add the nickel powder treated in step 1, perform ultrasonic stirring for 30 minutes (the frequency of the ultrasonic cleaning machine is 50 kHz), then let it stand and settle for solid-liquid separation, and wash with deionized water until the solution is neutral for use.
[0035] Step 3: Add 1000 mL of deionized water and 0.5 g of silane coupling agent KH550 to a beaker, stir and mix, then add the nickel powder cleaned in step 2 and stir at 40 °C for 5 hours. After the reaction is completed, let it stand and settle for solid-liquid separation, wash with anhydrous ethanol 3-5 times, and then wash with deionized water until the solution is clear for use.
[0036] Step 4: Add 50 g of butyl titanate and 1000 mL of anhydrous ethanol into a beaker, stir to mix, then add 50 g of 36.5% dilute acetic acid and the nickel powder cleaned in step 3 in turn, stir at 500 rpm, add 50 g of deionized water at a rate of 1 ml / min, continue the reaction for 5 h after the addition is completed, let it stand and settle for solid-liquid separation, and wash with ethanol 3-5 times. The washed wet powder is placed in a high-temperature drying oven and dried at 60 °C to obtain titanium dioxide-coated nickel powder.
[0037] Step 5: Add the titanium dioxide-coated nickel powder obtained in step 4, 1000 mL of deionized water and 10 g of ammonium citrate to a beaker and stir for 30 min. Then move to an oil bath, add 40 g of L-ascorbic acid and stir at 80 °C to prepare a dispersed solution. Add sodium hydroxide solution during the process to adjust the pH value of the solution to 12-13. Step 6: Take another beaker, add 10 g of silver nitrate and 1000 mL of deionized water into the beaker, stir ultrasonically, then add 20 g of ethylenediaminetetraacetic acid and stir for 30 min, add the complexed silver source to the dispersed solution in step 5, stir at 40°C and 300 rpm for reaction, settle after the reaction to separate the solid and liquid, wash the solution with deionized water until it is clear, wash it twice with anhydrous ethanol, and place it in a 60°C forced air drying oven for 4 h to obtain the following: Figure 2 The composite powder 2 shown.
[0038] Example 3 Step 1: Add 3g OP-10 and 1000mL deionized water to a beaker, stir to dissolve, add 10g nickel powder to the OP-10 solution, stir by ultrasonic, and then let it stand for sedimentation, then wash twice with anhydrous ethanol and three times with deionized water for use.
[0039] Step 2: Add 1000 mL of deionized water and 10 g of 98.3% sulfuric acid in a beaker, stir and mix, then add the nickel powder treated in step 1, perform ultrasonic stirring for 30 minutes (the frequency of the ultrasonic cleaning machine is 50 kHz), then let it stand and settle for solid-liquid separation, and wash with deionized water until the solution is neutral for use.
[0040] Step 3: Add 1000 mL of deionized water and 0.5 g of silane coupling agent KH550 to a beaker and stir to mix. Then add the nickel powder cleaned in step 2 and stir to react at 40 °C for 5 hours. After the reaction is completed, let it stand and settle for solid-liquid separation, wash with anhydrous ethanol 3-5 times, and then use deionized water to wash until the solution is clear for use.
[0041] Step 4: Add 50 g of butyl titanate and 1000 mL of anhydrous ethanol into a beaker, stir to mix, then add 25 g of 36.5% dilute acetic acid and the nickel powder cleaned in step 3 in turn, stir at 500 rpm, add 25 g of deionized water at a rate of 1 ml / min, continue the reaction for 5 hours after the addition is completed, let it stand and settle for solid-liquid separation, and wash with ethanol 3-5 times. The washed wet powder is placed in a high-temperature drying oven and dried at 60 °C to obtain titanium dioxide-coated nickel powder.
[0042] Step 5: Add the titanium dioxide-coated nickel powder obtained in step 4, 1000 mL of deionized water and 5 g of polyvinyl pyrrolidone to a beaker and stir for 30 min. Then move to an oil bath, add 40 g of L-ascorbic acid and stir at 40°C to prepare a dispersed solution. Add sodium hydroxide solution during the process to adjust the pH value of the solution to 12-13. Step 6: Take another beaker, add 10 g of silver nitrate and 1000 mL of deionized water into the beaker, stir ultrasonically, then add 20 g of ethylenediaminetetraacetic acid and stir for 30 min, add the complexed silver source into the dispersion in step 5, stir at 40°C and 300 rpm, react, settle after the reaction, separate the solid and liquid, wash the solution with deionized water until it is clear, wash twice with anhydrous ethanol, place in a 60°C forced air drying oven for 6 h, and obtain the following: Figure 3 The composite powder 3 shown.
[0043] Comparative Example 1 Preparation Figure 4 The composite powder 4 shown in the figure has a preparation step different from that of Example 1 only in that the addition of sodium hydroxide is omitted in step five.
[0044] Comparative Example 2 Preparation Figure 5 The composite powder 5 shown in the figure has a preparation step different from that of Example 1 only in that step 4 and step 5 are omitted.
[0045] The resistance of the composite powders prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test data are shown in Table 1. Table 1
[0046] from Figure 1-5 From Table 1, we can see that: 1. In the SEM images of Examples 1-3, the particles are well adhered, while in the SEM images of Comparative Example 1-2, the particles are distributed in a dotted manner, and there is no obvious adhesion between the particles. It can be seen that the composite powders (Examples 1-3) prepared by the preparation method of the present invention have better coverage and coating smoothness, among which Example 1 has the best coverage.
[0047] 2. The resistivity and high-temperature oxidation resistance of Examples 1-3 are significantly lower than those of Comparative Examples 1-2, and the smaller the resistivity, the higher the coating rate; the smaller the high-temperature oxidation resistance, the lower the degree of excessive oxidation of the nickel surface by the gas under high-temperature atmosphere. It can be seen that the composite powder prepared by the preparation method of the present invention has good coating density, which effectively inhibits the phenomenon of gas oxidation on the surface of the nickel layer through the gaps in the coating layer.
[0048] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite powder with a core-shell structure, characterized in that: The method comprises pretreatment of nickel powder, titanium dioxide coating treatment, plating solution treatment, and silver coating treatment in sequence, wherein: The titanium dioxide coating treatment comprises: adding butyl titanate and anhydrous ethanol in a reaction container in sequence, stirring and dispersing with ultrasonic stirring, and then adding dilute acid to obtain a reaction solution; adding the pretreated nickel powder into the reaction solution for constant temperature reaction, and after the reaction, sequentially performing solid-liquid separation, washing, and drying to obtain titanium dioxide coated nickel powder; The plating solution treatment comprises: adding titanium dioxide coated nickel powder, solvent and dispersant in a reaction container in sequence, stirring and dispersing by ultrasonic stirring, and then moving to an oil bath pot for constant temperature stirring, adding a reducing agent and sodium hydroxide solution during the constant temperature stirring process, and obtaining a dispersed solution after reaction; The silver coating treatment comprises: taking another reaction container and adding silver nitrate and deionized water, after ultrasonic stirring and dispersion, adding a complexing agent to carry out a complexing reaction; under stirring, slowly adding the complexed silver source reaction liquid to the dispersed solution for reaction, and after the reaction, sequentially performing solid-liquid separation, washing, and drying to obtain a composite powder.
2. The preparation method according to claim 1, characterized in that: The pretreatment includes degreasing treatment, coarsening treatment and activation treatment performed in sequence. The degreasing treatment includes adding nickel powder and a surface cleaning agent into a reaction container, allowing to stand and settle after ultrasonic stirring for solid-liquid separation, and washing the settled nickel powder with deionized water for multiple times; the coarsening treatment includes adding the degreasing nickel powder and dilute acid into the reaction container in sequence, allowing to stand and settle after ultrasonic stirring for solid-liquid separation, and washing the settled nickel powder with deionized water for multiple times; the activation treatment includes adding the coarsening nickel powder, deionized water and a surfactant into the reaction container in sequence, stirring at a constant temperature until the reaction is completed, allowing to stand and settle for solid-liquid separation, and washing the settled nickel powder with deionized water for multiple times.
3. The preparation method according to claim 2, characterized in that: During the degreasing treatment, the surface cleaning agent is at least one of citric acid, dodecylphenol polyoxyethylene ether, anhydrous ethanol, lauric acid alkylamine phosphate, and fatty alcohol ether sodium sulfate, and the mass ratio of the surface cleaning agent to the nickel powder is 0.01 to 1:
1.
4. The preparation method according to claim 2, characterized in that: During the roughening treatment, the dilute acid is one of dilute sulfuric acid, dilute acetic acid, and dilute hydrochloric acid, and the mass ratio of the dilute acid to the nickel powder after the degreasing treatment is 5 to 15:
1.
5. The preparation method according to claim 2, characterized in that: During the activation treatment, the surfactant is a silane coupling agent, and the mass ratio of the surfactant to the nickel powder after the roughening treatment is 0.01 to 1:
1.
6. The preparation method according to claim 1, characterized in that: During the titanium dioxide coating treatment, the mass ratio of the dilute acid to butyl titanate is 0.1 to 1:1, and the temperature of the isothermal reaction is 20 to 80°C.
7. The preparation method according to claim 1, characterized in that: During the plating solution treatment, the solvent is at least one of deionized water, anhydrous ethanol, ethylene glycol, and propylene glycol; the dispersant is at least one of polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfate, and ammonium citrate; and the reducing agent is at least one of glucose, L-ascorbic acid, hydrazine hydrate, and sodium hypophosphite.
8. The preparation method according to claim 1, characterized in that: During the plating solution treatment, the amount of sodium hydroxide solution added is such that the pH value of the dispersed solution is maintained between 12 and 13.
9. The preparation method according to claim 1, characterized in that: During the silver coating treatment, the complexing agent is at least one of ammonia water, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, diethylenetriamine, and triethylenetetramine, and the mass ratio of the complexing agent to silver nitrate is 1 to 50:
1.
10. A composite powder with a core-shell structure, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for core-shell structural nickel-silver bimetallic powder
CN102672168A
Preparing method of TiO2 (titanium dioxide) coated nanometer nickel powder
CN104057082A
Monodispersed spherical titanium dioxide core-shell structure composite material and preparation method thereof
CN104607185A
Nano material for SERS detection and preparation method and application thereof
CN110961620A
Electrically conductive particle, composition, article and method of manufacturing electrically conductive particle
CN111386580A
Cited By
Weldable low-temperature sintering type low-cost wear-resistant silver-coated nickel paste
CN121439317A
Weldable low-temperature sintered wear-resistant silver-coated nickel paste
CN121439317B